'It's not OK to shoot and kill Americans': families' perceptions of police use of lethal force in the United States. Issue 5 (19th October 2020) - Baker, David; Fidalgo, Marta
ABSTRACT: This article examines the police use of lethal force against American citizens from the perspective of families affected by these deaths. It is based on qualitative research undertaken with family members who lost loved ones after police contact in the United States. The article examines how organizational practices and cultures are perceived to enable the use of lethal force, and how multiple narratives are employed to legitimize its use in the aftermath of a citizen's death. It considers how procedural justice might provide a framework that enables an understanding of how these deaths are perceived by sections of US society. Key findings are that families believe police uses lethal force with relative impunity due to an aggressive mindset and a lack of effective regulation. The article further finds that symbolic legitimation strategies reward officers for using lethal force, and denigrate the deceased enabling these deaths to be classified as justified.